Faktor-Faktor yang Mempengaruhi Perilaku Penundaan Usia Kehamilan Remaja Menikah Usia Kurang 20 Tahun di Blora - Yuni Astuti; M. Zainal Abidin; Siswoko Siswoko (JURNAL KEBIDANAN, 2013)
There is a high number of Maternal Mortality Rate (164.5 per 100.000 live births) during the year of 2011 at Blora District. This number is far below MDG’s target. The aim of this study was to find out factors influence delaying pregnancy of adolescents under 20 years o1ld in Blora. This study is an explanatory research and uses cross sectional approach. The subjects consisted of 152 adolescents who had marriage under 20 years old in 2011. Tehnical sampling used in this study was purposive sampling. Data was gained at May 21th 2012 until August 2nd 2012. The data was analysed by frekuency distribution. Chi Square was used to find the correlation between variables. Moreover, logistic statistic test was used as multivariatee analyses. The results showed that 54,6% of them delayed their pregnancy. The study revealed that there were strong correlation between delaying pregnancy with the age of marriage, attitude toward delaying pregnancy and couple support for delaying pregnancy. The variables which influence behavior of delaying pregnancy among respondents are couple support for delaying pregnancy. The most influential factor is and couple support for delaying pregnancy.